EFEKTIVITAS PROGRAM DIGITAL NATIVES ENTREPRENEUR DALAM MEMBANGUN PSYCHOLOGICAL CAPITAL PADA PENGUSAHA MUDA DI MASA PANDEMI COVID-19: THE EFFECTIVENESS OF DIGITAL NATIVES ENTREPRENEUR PROGRAM IN BUILDING PSYCHOLOGICAL CAPITAL ON YOUTH ENTREPRENEUR IN THE COVID-19 PANDEMIC ERA - M Shafwan; Chindy Kadora; Khoiri Esa (Jurnal Psikologi Jambi, 2022)
ABSTRACT Introduction The covid-19 pandemic presents challenges in the business world, with the decline in the number of entrepreneurs and the fear of developing their own business. The main problem is the lack of mental readiness of entrepreneurs in entrepreneurship. So, psychological capital has an important role to play in building an entrepreneurial mentality in the younger generation in entrepreneurship during the covid-19 pandemic era. This study aims to determine the effectiveness of the digital natives entrepreneur training program to build psychological capital for young entrepreneurs during the covid-19. Method This research is a quantitative research that uses a quasi-experimental research. The population in this study were PMW Jambi University students in 2019-2021, with a total sample of 24 people. The analysis carried out is descriptive analysis, Independent Sample t-test and Paired Sample t-test using the JASP0.14.1.0 application. Results This study shows that there is a significant effect of psychological capital on young entrepreneurs before and after being given the digital natives entrepreneur program with a sig value. of 0.006 < 0.05. The results of this study also showed that the average value of the experimental group was 84.9, which was higher than the control group which was 81.7. Conclusion and Recommendation It is concluded that there is a significant difference in Psychological capital in young entrepreneurs before and after being given the digital natives entrepreneur program. Therefore, with the results of this study, it is important to build mental readiness in entrepreneurship, so that individuals have self-confidence, fighting spirit and business mentality that make individuals consistent in running and developing their business. Keyword : Psychological capital, Digital natives entrepreneur, Young entrepreneur